Landscape into Eco Art : Articulations of Nature Since the '60s - Cheetham, Mark A. (Mark Arthur), 1954- (Book collections on Project MUSE., 2018)
"Explores the practices of ecological art, a genre addressing the widespread public concern with rapid climate change and related environmental issues. Examines connections and divergences between contemporary eco art, land art of the 1960s and '70s, and the historical genre of landscape painting"--Provided by publisher